Analysis of Shifts in Product Quality using The Individual-Moving Range and Cumulative Sum Fast Initial Response Methods - Ramayani Nur Hadiati; Sherli Yurinanda; Sarmada (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2026)
Abstract: Quality control plays an important role in maintaining production consistency, especially in manufacturing industries such as PT Wirakarya Sakti in Jambi Province. The company faces instability in daily production in achieving the target of 1,044.82 tons. This study aims to analyze the ability of the Individual-Moving Range (I-MR) and Cumulative Sum Fast Initial Response (CUSUM FIR) methods to detect shifts in production quality based on quantitative daily production data, as well as to determine the method that is more sensitive to process instability. The study employed a Statistical Quality Control (SQC) approach through the construction of I-MR and CUSUM FIR control charts. The results showed that the I-MR control chart detected significant fluctuations, with several points exceeding the control limits, while CUSUM FIR was more sensitive in detecting small shifts and was able to provide earlier signals of out-of-control conditions. Therefore, the CUSUM FIR method is considered more effective as an early detection tool for maintaining production process stability, whereas the I-MR method is more suitable for detecting large-scale shifts. Abstrak: Pengendalian kualitas penting untuk menjaga konsistensi hasil produksi, terutama di industri manufaktur seperti PT Wirakarya Sakti di Provinsi Jambi. Perusahaan menghadapi ketidakstabilan produksi harian dalam mencapai target sebesar 1.044,82 ton. Penelitian ini menganalisis kemampuan metode Individual-Moving Range (I-MR) dan Cumulative Sum Fast Initial Response (CUSUM FIR) dalam mendeteksi pergeseran kualitas hasil produksi berdasarkan data produksi harian, serta menentukan metode yang lebih sensitif terhadap ketidakterkendalian proses. Penelitian menggunakan Statistical Quality Control (SQC) melalui pembentukan peta kendali I-MR dan CUSUM FIR. Hasil analisis menunjukkan peta kendali I-MR mendeteksi adanya fluktuasi signifikan dengan beberapa titik melampaui batas kendali, sedangkan CUSUM FIR lebih sensitif mendeteksi pergeseran kecil dan mampu memberikan sinyal ketidakterkendalian lebih awal. Metode CUSUM FIR lebih efektif digunakan sebagai alat deteksi dini untuk menjaga kestabilan proses produksi, sementara I-MR lebih sesuai untuk mendeteksi pergeseran dalam skala besar.